Code of a killer [videorecording (DVD)] - Crompton, Michael; Threlfall, David; Simm, John; Madeley, Anna, 1977-; Deol, Jaz; Cranitch, Lorcan, 1959-; Tiernan, Andrew, 1965- (Acorn Media, 2017)
A three-part British police drama tells the true story of scientist Alec Jeffrey's discovery of DNA fingerprinting in the 1980s and its introductory use by Detective Chief Superintendent David Baker in catching a double murderer.